Evaluation of Exposure of Radio Frequency Field (RF) Radiation from Mobile Communication Base Stations in Port Harcourt, Rivers State, NigeriaQ - , U. Nte Felix; , O. Avwiri Gregory; , C. P. Ononugbo; , E. Esi Oghenevovwero (Archives of Current Research International, 2017)
The work evaluates the exposure of radio frequency field (RF) radiation from Mobile Communication Base Stations in Port Harcourt, Rivers State, Nigeria. The instruments used in this study include: RF field strength meter, a portable meter and a GPS. Some locations within Port Harcourt City were selected which include: Rumuokoro, Mile 3, Garrison and Mile 1. The readings were taken from 5 m to 400 m from the telecommunication base stations at about 1.5 m above the ground. The total average amount of radiation measured from different locations were 22.475 µW/cm2 for Rumuokoro, 26.906 µW/cm2 for Mile 3, 34.286 µW/cm2 for Mile 1 and 22.876 µW/cm2 for Garrison with their corresponding values of coefficient of correlation as -0.52, -0.46, -0.788, and -0.831 respectively. Since this study revealed that the RF exposure hazard index in the Port Hancourt City was below the permitted RF exposure limit to the general public recommended by ICRNIP and WHO, it is highly likely there is no significant impact on human health.